P077 Different granulocyte subsets are involved in the pathogenesis in Crohn's disease fistula. (21st January 2022) - Becker drs, M; Koelink, P; de Krijger, M; Bemelman, W; de Jonge, W; Buskens, C; Wildenberg, M
Abstract: Background: Early in inflammation granulocytes migrate from the circulation into inflamed areas and rapidly accumulate. They form an important role in first defense as well as the orchestration of downstream immune responses. In the circulation, several different subsets of granulocytes have been described, for example immature, intermediate and mature granulocytes. Surprisingly, despite their abundance and prominent function, this cell type is rarely studied from a tissue perspective, most likely due to their short lifespan ex vivo. One example of gastrointestinal disease with an extremely high number of granulocytes is the occurrence of perianal fistula which contain a considerable amount of granulation tissue. As curettage of this tissue is part of the treatment, the fistula tract is good source to study tissue derived granulocyte subsets. The aim of this study was to characterize granulocyte subsets in the fistula tract. Methods: Curettage material of perianal fistula tracts was obtained during surgical intervention from patients with CD (n=15) and cryptoglandular fistulas (n=5). From 2 CD patients venous blood was taken and a ficoll step was performed. Single-cell suspensions were stained with a 35-antibody panel, including CD66, CD14, CD33, CD16 and CD11b. Samples were analyzed using mass cytometry (CyTOF). Results: Granulocytes, characterized as CD45+CD66a+ cells, were the main cellular component of the fistula tract (64%±24) compared to other immune cells. This was more pronounced in cryptoglandular fistula compared to CD fistula (81% vs. 67%; p=0.019). Within these cells we could differentiate between 4 subsets, mature granulocytes (CD33 + CD11b + CD16 + ), intermediate (CD33 int CD11b + CD16 int ), immature granulocytes (CD33 int CD11b - CD16 int ) and eosinophils (CD33 - CD11b - CD16 - ). Immature granulocytes were the most abundant in de fistula tract (31%±15), closely followed by the mature (30%±23) and intermediate (23±9). No significant difference was seen in the percentages of granulocyte subsets between CD and cryptoglandular fistula. Conclusion: Here, we show the presence of different subtypes of granulocytes in fistula derived granulation tissue. We show a heterogeneous group of cells ranging from immature neutrophils to mature neutrophils. Due to their high number in active ulcerating tissue, further evaluation of granulocyte subsets and function could be an interesting target for medical treatment options.